Community of Policy Practice (CoPP) - CGIAR (CGIAR System Organization, 2023)
In June 2023, a dedicated team coalesced, its members drawn together by a shared passion for advancing policy research and praxis in Ethiopia. With a series of focused meetings, the team discussed the findings of the IAA (Institutional Architecture Assessment) for Ethiopia and map out future directions in policy research and praxis during its kick-off meeting. The NET-PARAF Core Team (Network for Ethiopian Policy Analysis and Research in the Agriculture and Food System) again converged to deliberate upon the pathways delineated during the Launching Workshop, assessing the viability of proposed strategies and meticulously plotting the trajectory for forthcoming endeavors. This collaboration is part of the CGIAR Initiative on National Policies and Strategies’ (NPS) ‘Communities of Policy Practice (CoPP) and Cross-Coutnry Learning’ program.